A comparative study of phytochemical investigation and antioxidative activities of six citrus peel species. (31st May 2021) - Olfa, Taktak; Gargouri, Manel; Akrouti, Amel; Brits, Maxime; Gargouri, Mahmoud; Ben Ameur, Raoudha; Pieters, Luc; Foubert, Kenn; Magné, Christian; Soussi, Ahlem; Allouche, Noureddine
Abstract: Over the past few decades, much effort has been devoted to the study of known food products for medicinal applications. Among these, citrus fruits play a key role in providing a wide range of health‐beneficial effects but it generates a huge amount of waste products. In an attempt to recover those wastes, peel of six citrus species ( C aurantium, C limetta, C limon, C reticulata, C Sinensis osbeck, and C Sinensis thomson) was evaluated for yield, physicochemical properties, phenolic constituents and antioxidant activities. LC‐MS/MS analysis showed that the flavonoids neoeriocitrin, luteolin‐7‐ O ‐neohesperidoside, scoparin and neohesperidin were chemical markers for C limetta, whereas apigenin‐6, 8‐di‐ C ‐glycoside was only detected in C Sinensis Osbeck . PCA analysis revealed signiﬁcant correlations between antioxidant activities and phenolic contents, highlighting a large interspecific variability. These results suggest that Citrus peel by‐products may be valuably recycled by industries due to their high yield and transformed into value‐added products, with potential interest for the development of functional foods, cosmetics or preventive therapies for some diseases. Abstract : Peel of citrus fruits contains a large diversity of bioactive components, thus is considered as potential sources of functional constituents. The aim of this study was to characterize ethanol extracts of citrus fruit peels according to antioxidant abilities, as well as phenolic constituents. LC‐MS/MS analysis of six citrus species showed for the first time that flavanones were the main phenolic components in the peel extracts. PCA analysis revealed a significant correlation between antioxidant activities and phenolic contents. Moreover, physicochemical analyses revealed the highest sugar content in C limon extract, whereas C reticulata exhibited the highest ash and water contents. Overall, peels of C limon, C limetta and C reticulata fruits appear to be a useful waste product for industrial production of new functional ingredients.